Garçon Manqué: A Queer Rereading (of) The Sheik - Jessica Taylor (Journal of Popular Romance Studies, 2020)
This article reads E.M. Hull’s The Sheik (1919) through the lens of queer and trans studies, centering the analysis on the beginning of the book where Diana Mayo, the main character, is portrayed as an imperial boy. Starting with a consideration of how the readership of the novel has been used to interpret The Sheik, I argue that a focus on a heterosexual woman reader who herself desires the novel’s hero, Sheik Ahmed Ben Hassan, has obscured the queerness of Diana’s gender. Instead, I consider how we might read Diana with a trans lens and take seriously her masculinity, paying attention to the opening of the book rather than the ending where her ordeals and developing love for Ahmed have rendered her womanly. Diana’s initial masculinity crucially intersects with her English imperialism and her identification with the position of masculine power. I compare The Sheik to another interwar British novel with a masculine heroine—Radclyffe Hall’s The Well of Loneliness (1928). While The Well of Loneliness places its heroine within a queer framework, it is ironically in part because of The Sheik’s lack of positioning of Diana within any queer or trans community or identity category that the novel can be read as presenting an alternate vision of past trans joy. Finally, I consider how lingering on Diana’s masculinity reveals her and Ahmed Ben Hassan as doubles of each other, each exploring the ambiguities of inheritance and upbringing in both gender and race. While some readings might then focus on what this reveals about the instabilities of gender, I end with a trans reading that instead embraces Diana’s attachment to her boyhood, before the plot closes off that possibility.